B2B portal: Web-enable fulfillment system / Wong Oi Ching - Wong, Oi Ching (2001)
The Web-enable fulfillment system is basically a web site that enables suppliers to automate and structure the order fulfillment process to help ensure that products and services meet or exceed customer’s exact requirements including quality, quantity and specifications. The intelligence of the system will be the server where all calculations and business rules are applies. Business-to-business (B2B) e-Commerce implies that both the sellers and buyers are business corporation. Purchase order is used as the system default as the business partners rarely use credit card for payment. Therefore, the order fulfillment process begins when an approved order is routed to the supplier. The supplier begins to pick the products, allocate an appropriate warehouse, consolidate the products, deliver the products and etc. The process complete when every product in a particular order has been fulfilled. Web-enable fulfillment system is planned to be developed by using Microsoft Visual Interdev and Active Server Pages (ASP) technologies on the Window 2000 Server platform Microsoft SQL Server is used for the database purpose. With latest and powerful technology, the system is not expected to be workable, but also highly efficient in terms of execution speed and response time. The system design is dynamic and supporting concurrent users to interact with the system over internet.